Analysis of the use of Artificial Intelligence Technology on Digital Startups in Indonesia - Muhamad Rizal, Erna Maulina, Margo Purnomo, Aulia Rizki Wicaksono (International Journal of Advanced Science and Technology, 2020)
The application and adoption of Artificial Intelligence technology in Southeast Asia in 2018 has reached the level of 14%. According to statistics and SAS Asia Pacific research results in 2018 the spread of the application of AI technology in Asia has reached several business sectors ranging from banking, telecommunications, health, digital commerce, trade in goods and services. It is known that 26.4% of Indonesia, 17.1% of Thailand, 9.9% of Singapore, 8.1% of Malaysia has been able to adopt AI technology in their organizations. However, in reality, Indonesia still occupies the lowest position on the Asian Index of Artificial Intelligence (<0.2).